Perspektif Kebahagiaan Masyarakat yang Tinggal Dekat Tempat Pembuangan Akhir Sampah Di Samarinda - Hamka Hamka; Tri Astuti (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2019)
The final landfill is always identified with dirty, smelly and far from healthy lifestyles, things like that that ultimately do not encourage people to stay close to the landfill site. But in fact, there are many residents near the landfill. Although the distance living close to the mountains of waste, people feel happy life. People living close to the waste dump have lived for more than 10 years and have chosen to settle in the area. Therefore, happiness does not have to be in a beautiful and clean environment. This study aims to obtain information about the dynamics of happiness felt by residents living in landfills used in this study is a qualitative method with phenomenology approach. Data collection tools used are interviews and observation. The research analysis is used by using open encoding, axial coding and selective coding. Based on the results of the study it was found that people living near TPA feel happy because people there help each other despite the limitations of both housing and food. In addition, the public is happy because the workplace is close to where to live and there is no pressure in working. Keywords: Happiness, Final disposal, Trash, Community